TINJAUAN HUKUM ATAS CLICK WRAP AGREEMENT PADA KONTRAK BAKU ELEKTRONIK TERKAIT TRANSAKSI ELEKTRONIK - santoso, edy (Magister Ilmu Hukum Sekolah Pascasarjana Unida, 2015)
Nowadays, the development of technology information has tremendous impact on aspects of cultural, economic, social and legal. In the area of business transactions, for example, a signature is a common form of agreement in the purchase agreement. Today, it has been changed; the form agreement was made so simple by âclickâ only through using